2015
DOI: 10.3945/jn.114.209320
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Risk of Melanoma in an Italian Population

Abstract: These results suggest that diet quality may play a role in cutaneous melanoma etiology among women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 60 publications
4
40
0
Order By: Relevance
“…We also assessed their dietary habits through a semi-quantitative food frequency questionnaire used for the Central-Northern Italian population within the EPIC study (21). This questionnaire assessed the frequency and amount of consumption of 188 food items over the previous year, and allowed to estimate frequency and quantity of consumption of the individual foodstuff and related intake of nutrients and contaminants through an ad hoc software (22,23). With regard to the intake of such nutrients, we selected only those previously reported to influence Mn content, i.e., iron, calcium and phosphorus (6,7).…”
Section: Methodsmentioning
confidence: 99%
“…We also assessed their dietary habits through a semi-quantitative food frequency questionnaire used for the Central-Northern Italian population within the EPIC study (21). This questionnaire assessed the frequency and amount of consumption of 188 food items over the previous year, and allowed to estimate frequency and quantity of consumption of the individual foodstuff and related intake of nutrients and contaminants through an ad hoc software (22,23). With regard to the intake of such nutrients, we selected only those previously reported to influence Mn content, i.e., iron, calcium and phosphorus (6,7).…”
Section: Methodsmentioning
confidence: 99%
“…We also administered two questionnaires to all study subjects: one collected information on several variables including smoking habits and occupational history, the second investigated dietary habits through a semi-quantitative food frequency questionnaire used for the Central-Northern Italian population within the EPIC study (Pasanisi et al, 2002;Pala et al, 2003). This questionnaire assessed the frequency and amount of consumption of 188 food items over the previous year, and allowed the frequency and quantity of consumption of foodstuffs and the related intake of nutrients and contaminants to be calculated using an ad hoc software (Malavolti et al, 2013;Malagoli et al, 2015). This database included among other trace elements selenium and Cd, and was largely based on chemical analyses of foodstuffs distributed in Northern Italy performed at the University of Modena and Reggio Emilia for both selenium (Vinceti et al, 2015b) and Cd (Bottecchi and Vinceti, 2012;Malavolti et al, 2015).…”
Section: Study Participantsmentioning
confidence: 99%
“…Fortes and colleagues (27) found the Mediterranean diet may have protective effects against melanoma. Malagoli and colleagues (88) found an inverse association between melanoma risk with the Healthy Eating Index 2010 (HEI-2010) and Dietary Approaches to Stop Hypertension (DASH) index, which both assess diet quality. These lines of evidence suggested that dietary patterns could affect risk of melanoma.…”
Section: Discussionmentioning
confidence: 99%